Biohydrometallurgy for Cobalt Recovery from Spent Li-ion Batteries using Acidophilic Bacteria Isolated from Acid Mine Drainage - Asful Hariyadi; Umi Sholikah; Bangkit Gotama; Muhammad Abdul Ghony (CHEMICA: Jurnal Teknik Kimia, 2022)
Nowadays, recycling Li-ion batteries is an important thing to do to minimize the risk of exposure to this hazardous solid waste. On the other hand, extracting these materials can optimize the economic potential of valuable minerals in the active cathode. Bioleaching was developed as an environmentally friendly method to extract cobalt from the cathode by utilizing the metabolic activity of A. ferrooxidants cells. Microorganisms were isolated from Acid Mine Drainage in a 9K liquid medium at pH=2.5 and used as an inoculum. The Bioleaching process was carried out with various cell concentrations of 5, 10, and 20 %v/v. A positive response was shown by monitoring the microorganism activity through changes in physical appearance, decreasing the pH value, and increasing the Fe3+ concentration. The structural analysis of cathode by XRD and SEM has shown the effect of Co dissolution before and after bioleaching. Optimum recovery of cobalt was achieved up to 57.81% after 14 days of incubation.